Aircraft Modeling and Simulation - Botez, Ruxandra Mihaela; Grigorie, Teodor Lucian; Sugar-Gabor, Oliviu; Murrieta-Mendoza, Alejandro (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Various aerodynamics, structural dynamics, and control design and experimental studies are presented with the aim of advancing green and morphing aircraft research. The results obtained with an in-house CFD code are compared and validated with those of two NASA codes. The aerodynamical model of the UAS-S45 morphing wing as well as the structural model of a morphing winglet are presented. A new design methodology for oleo-pneumatic landing gear drop impact dynamics is presented as well as its experimental validation. The design of a nonlinear dynamic inversion (NDI)-based disturbance rejection control on a tailless aircraft is presented, including its validation using wind tunnel tests.